CERVICAL CYTOLOGY EXAMINATION: INQUIRY INTO THE KNOWLEDGE, ATTITUDE AND PRACTICE OF PREGNANT WOMEN - Ana Raquel Rodrigues Rosa; Tayane Siqueira de Lima e Silva; Izabel Cristina da Silva Carvalho; Antônia Sylca de Jesus Sousa; Ângelo Brito Rodrigues; Jardeliny Corrêa da Penha (Universidade Federal do Paraná, 2018)
Objective: to verify the knowledge, attitude and practice regarding the cervical cytology examination of pregnant women assisted in the Family Health Strategy. Method: Knowledge, Attitude and Practice inquiry developed with 46 pregnant women attended in primary health unitsof Floriano, Piauí state. Data collection was carried out from May to July 2016, with the application of a previously elaborated instrument. Descriptive analysis was performed, with the Chi-square test for the association of the nominal variables. Results: thepregnant women presented inadequate knowledge, attitudes and practices regarding the cytology examination. There was a significant association of some variables with the practice of pregnant women in relation to cervical cytology (examination can be performed during pregnancy, p=0.030, reason why the test would be performed during pregnancy, p=0.043). Conclusion: pregnant women need to understand the cervical cytology examination and the importance of its performance during pregnancy, in order to be able to adhere to the practice of performing the examination.